2018
DOI: 10.1038/s41408-018-0124-1
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for acquisition, interpretation and reporting of whole body low dose CT in patients with multiple myeloma and other plasma cell disorders: a report of the IMWG Bone Working Group

Abstract: Whole Body Low Dose CT (WBLDCT) has important advantages as a first-line imaging modality for bone disease assessment in patients with plasma cell disorders and has been included in the 2014 International Myeloma Working Group (IMWG) criteria for multiple myeloma (MM) definition. Nevertheless, standardization guidelines for the optimal use of WBLDCT in MM patients are still lacking, preventing its more widespread use, both in daily practice and clinical trials. The aim of this report by the Bone Group of the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 33 publications
1
69
0
Order By: Relevance
“…The widespread availability of multi-detector CT scanners has contributed to the increased use of WBLDCT for the diagnosis and follow-up of MM. The total effective dose of the WBLDCT in our study is comparable to those reported in recent literature [24][25][26][27]. Moreover, our measured organ specific dose is comparable to the organ dose described by Kröpil DLP dose length product, CTDI vol volume computed tomography dose index, NA not applicable/available et al [28].…”
Section: Discussionsupporting
confidence: 88%
“…The widespread availability of multi-detector CT scanners has contributed to the increased use of WBLDCT for the diagnosis and follow-up of MM. The total effective dose of the WBLDCT in our study is comparable to those reported in recent literature [24][25][26][27]. Moreover, our measured organ specific dose is comparable to the organ dose described by Kröpil DLP dose length product, CTDI vol volume computed tomography dose index, NA not applicable/available et al [28].…”
Section: Discussionsupporting
confidence: 88%
“…In line with this concern, neither in IMWG [ 9 ] nor the recently published ESMO guidelines [ 18 ] took into account the inner density of lesion detected by WB-LDCT. In addition, recently published recommendations from IMWG on interpretation of WB-LDCT suggest that the presence of fat-containing foci excludes the diagnosis of osteolysis, provided that the patient has not been previously treated [ 19 ]. Concordance between WB-LDCT and PET is reported to be higher than 85% [ 20 ] while concordance between WB-LDCT and MRI is roughly 70% [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In MM, the bone lesions of myeloma are determined by the proliferation of cells from a single clone. Then, osteoclasts are activated and destroy the bone [1]. MM, known with the abbreviation CRAB (hyperCalcemia, Renal failure, Anaemia, and lytic Bone lesions) is a cytogenetically heterogenous disorder of clonal plasma cells [1].…”
Section: Introductionmentioning
confidence: 99%
“…Then, osteoclasts are activated and destroy the bone [1]. MM, known with the abbreviation CRAB (hyperCalcemia, Renal failure, Anaemia, and lytic Bone lesions) is a cytogenetically heterogenous disorder of clonal plasma cells [1]. The extent of the bone disease negatively influences patients' quality of life, increasing both morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation